(untitled) (Revista de Ensino em Artes, Moda e Design, 2024)
The interview arises from discussions about the series "Interviewing in the Art Room" on the Laboratório Interdisciplinar de Formação de Educadores (LIFE) channel on YouTube. Launched in 2019, the series aims to interview elementary school teachers engaged in Pedagogia Histórico-Crítica (PHC). With 8 interviews to date, after a period of inactivity, we decided to interview Professor Maria Cristina da Rosa Fonseca da Silva, a central figure in both the series and our studies on PHC in our teaching and academic careers. The initiative to conduct the interview originated during the course "Special Topic: Teaching Visual Arts Today," held in 2023/2 by the Graduate Program in Visual Arts (PPGAV/UDESC). The interview was proposed as an evaluative activity, aligning with the goal of engaging with teachers conducting research related to contemporary visual arts education. We chose to interview Professor Maria Cristina, our advisor, whose teaching journey and significant research contribute to the field of Visual Arts education. Thus, the interview provides not only a review of the series and its revival but also a reflection on the influence of PHC on our studies and teaching practice. It emphasizes the importance of Professor Maria Cristina as a reference in Visual Arts education based on Historical-Dialectical Materialism.